Manipulation of translation in hard news reporting on the Gulf crisis: combining narrative and appraisal - Boéri, Julie; Fattah, Ashraf (Meta, 2020)
This paper explores the manipulation of translation for propagandistic purposes in the Gulf crisis, which has led to the economic blockade of Qatar since June 2017. It focuses on Al-Ittihad, an Arabic daily newspaper owned by the United Arab Emirates. The data under analysis is extracted from a hard news daily section that Al-Ittihad has dedicated to Qatar since the outbreak of the crisis. Combining Narrative Theory with the Appraisal Framework provides an insightful account of the ideologically motivated manipulation and weaponization of news translation. Going beyond the reductive claim of domestication in News translation studies, this dual theoretical approach allows for further articulation of the socio-political context with translation strategies, by combining macro- and micro-analysis. This approach also uncovers the workings of propaganda in Al-Ittihad’s translational news reporting. From the transediting of foreign attributions to the intersemiotic design of the newspaper’s layout, translational news reporting involves embedding personal and shared narratives into the micro- and macro-levels of the hard news section to construe a negative evaluation of Qatar. Behind a façade of detachment and neutrality, hard news reports and the translation on which they rely feed into the propagandistic discourse of hawkish parties.